Social Participation: A Good Life After Retirement in Russia - Liliya Martynova; Jiby Mathew Puthenparambil (Research on Ageing and Social Policy)
Social activities that older adults engage in are vital to social policy on ageing in Russia. This study looks from the eudaimonic perspective at the participation of older adults in three Russian social projects featuring activities in volunteering, fashion modelling and traditional handicrafts. Qualitative and quantitative methods were applied to analyse 934 completed online surveys. Despite differences in the types of activities, the results showed that satisfaction with fulfilling older adults' motivations to participate and the benefits they gained from participation led to improvements in their perceptions of life after retirement. According to the participants, additional indicators such as the sense of being needed, the feeling of happiness, and self-assessment of health also improved. However, organising social activities requires flexibility to meet older people’s heterogeneous needs and interests according to changes in their personal situation or the external environment. To achieve a sense of well-being in older age, these activities must satisfy internal motivations to participate and should cover essential needs of relatedness, competence, and autonomy.